Training physicians to work in a second language - Szymańska, Oliwia (Folia Scandinavica Posnaniensia, 2024)
This study highlights the importance of targeting practices that facilitate physician-patient communication in language courses for health professionals. The aim of this study is twofold. Firstly, it examines if and how physicians with a second language deploy metaphors to facilitate understanding. Secondly, it investigates how this practice can be enhanced through communicative training. The study comprises two separate parts, each with a different approach, method, and participants. Study 1 investigates the use of metaphors in authentic situations from outpatient clinics, where physicians consulted patients in L2 Norwegian. The data consists of transcripts of video recordings and an interview with one of the physicians. Study 2 examines the outcomes of an intervention during an intensive language course before the physicians’ arrival in Norway. The data in this study include oral and written production, as well as an interview with one of the participants. Study 1 revealed contexts in which migrant physicians deploy metaphors to facilitate their communication in L2 and types of the expressions they use. Study 2 showed that stimulating metaphor awareness might be beneficial for metaphor use in communication and comprehension in visual representation, which in turn can support L2 communication in the physicians’ everyday practices.